Analisis Pengaruh Attitude toward The Destination dan Brand Awareness terhadap Brand Preference dengan mediasi Destination Image dan Brand Equity pada Wisata Pantai Kota Batam - Lily Purwianti; Muhammad Adjie (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Brand Preference is defined as behavior that shows consumer attitudes towards a brand. Created from an experience that is sensory, emotional, and creative, Brand Preference is very useful in the world of tourism. Of the various tourist beaches in Batam City, 5 of them are the most favorite beaches, namely Viovio Beach, Mirota Beach, Melur Beach, Tegar Bahari Beach, Elyora Beach. This study aims to analyze the influence of Attitude toward The Destination and Brand Awareness on Brand Preference by mediating Destination Image and Brand Equity on Batam City Beach Tourism. The results of this study indicate that the research model supports all the hypotheses that have been proposed.